2020
DOI: 10.1016/j.jor.2019.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Local flaps vs. free flaps for complex lower limb fractures: Effect of flap choice on patient-reported outcomes

Abstract: The optimal flap cover for managing open lower limb fractures is debated. Most studies have reported on surgical outcome but clinical outcome is not well recognised. We aimed to determine whether there are differences in patient-reported quality of life (QoL) outcome between local flap versus free flap.All patients admitted with lower limb open fractures were retrospectively reviewed. Patient notes were assessed for demographics, time to fracture union, wound healing and patient-reported QoL with EQ-5D-5L alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Defect aetiology varied greatly between and inside the selected studies including traumatism, neoplasm, infections, scar contractures, and chronic wounds (with peripheral vascular disease, irradiation, and neuropathy). Complete flap necrosis was reported in all 10 articles and the pooled analysis did not find a significant difference between FF and PF (RR 1.35, 95%CI 0.76-2.39, p = 0.31) [12][13][14][15][16][17][18][19][20][21]. (Figure 2) A partial flap failure was reported in eight articles and FF had a significantly lower risk than PF in the pooled analysis (RR 0.45, 95%CI 0.22-0.91, p = 0.03) [12][13][14][15][16][18][19][20] (Figure 3).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Defect aetiology varied greatly between and inside the selected studies including traumatism, neoplasm, infections, scar contractures, and chronic wounds (with peripheral vascular disease, irradiation, and neuropathy). Complete flap necrosis was reported in all 10 articles and the pooled analysis did not find a significant difference between FF and PF (RR 1.35, 95%CI 0.76-2.39, p = 0.31) [12][13][14][15][16][17][18][19][20][21]. (Figure 2) A partial flap failure was reported in eight articles and FF had a significantly lower risk than PF in the pooled analysis (RR 0.45, 95%CI 0.22-0.91, p = 0.03) [12][13][14][15][16][18][19][20] (Figure 3).…”
Section: Resultsmentioning
confidence: 89%
“…(Figure 2) A partial flap failure was reported in eight articles and FF had a significantly lower risk than PF in the pooled analysis (RR 0.45, 95%CI 0.22-0.91, p = 0.03) [12][13][14][15][16][18][19][20] (Figure 3). Overall complication rates were reported in six studies, and the pooled analysis found no significant difference between FF and PF concerning the overall risk of complications (RR 0.83, 95%CI 0.64-1.07, p = 0.16) [13,15,16,[19][20][21] (Figure 4). For Yuan et al's work, a vascular crisis was not counted as a complication, as it was defined as a clinical sign motivating surgical exploration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 Meanwhile, Bhullar et al reported a venous congestion rate of 8.7% in a lower limb reconstructed with local flaps, and of 23.5% in those reconstructed with free flaps. 8 …”
Section: Discussionmentioning
confidence: 99%
“…7 Meanwhile, Bhullar et al reported a venous congestion rate of 8.7% in a lower limb reconstructed with local flaps, and of 23.5% in those reconstructed with free flaps. 8 Venous congestion has an extrinsic or intrinsic etiology; the first one is related to mechanical causes and the second one, to microcirculatory problems. If the cause is extrinsic, it requires a return to the operating room.…”
Section: Discussionmentioning
confidence: 99%